EFFECTS OF MEDIUM COMPOSITION ON OXYTETRACYCLINE PRODUCTION BY STREPTOMYCES RIMOSUS ATCC 33022 - Linar Z. Udin; S. Pudjiraharti; A. T. Karossi (Research Center for Chemistry - LIPI, 1992)
The economical production of antibiotics to some extent depends on the availabilily of cheap substrates. The work reported in the present paper deals with the fermentative production of oxytetracycline by Streptomyces rimosus ATCC 33022 using commerciol high fructose syrup (HFS), vitamin B complex and citric acid of technical grode. The effects of concentration of high fructose syrup (0.5 - 2.5 %, v/v), commercial vitamin B complex (0.03 - 0.07 %, w/v) and the citric acid (0.34 - 1.28 %. w/v) were examined in this study. It was found that fermentation medium (medium-MHFS) containing high fructose syrup 1.0 % produced maximum activily of oxytetracycline after 4 days incubation period. Fermentation tnedium (mediwn-MBpleJ containing 0.05 % commerciol vitamin B complex showed maximum acrivily after 3 days incubation. While the addition of citric acid (0.64 %) to the fermentation medium (medium-MCA) was found optimumfor production oxytetracycline.